2020
DOI: 10.32598/jpr.8.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Neuromyelitis Optica Spectrum Disorders: Three Case Reports and Review of Literature

Abstract: Introduction: Neuromyelitis optica spectrum disease (NMOSD) is a rare autoimmune inflammatory astrocytopathic demyelinating disease of the CNS. In the majority of patients, an autoantibody to the water channel protein aquaporin-4 (AQP4) would cause humoral inflammatory demyelination and axonal damage. The disease defined as clinical syndromes of optic nerve, area postrema, spinal cord, diencephalon, or cerebrum or MRI finding related to involvement of these regions. According to recent consensus diagnostic cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…They studied the latest research progress on the role of microglia in the pathogenesis of NMOSD, the mechanisms of microglia activation and microglia-mediated inflammation, and potential research prospects [ 8 ]. Research by Baghbanian et al showed that autoantibodies to the aquaporin 4 (AQP4) caused humoral inflammatory demyelination and axonal damage [ 9 ]. Zhang et al collected data on 40 patients with CTD LETM admitted to the Department of Neurology or Rheumatology, divided into two groups: CTD-LETM-NMOSD and CTD-LETM-non-NMOSD.…”
Section: Introductionmentioning
confidence: 99%
“…They studied the latest research progress on the role of microglia in the pathogenesis of NMOSD, the mechanisms of microglia activation and microglia-mediated inflammation, and potential research prospects [ 8 ]. Research by Baghbanian et al showed that autoantibodies to the aquaporin 4 (AQP4) caused humoral inflammatory demyelination and axonal damage [ 9 ]. Zhang et al collected data on 40 patients with CTD LETM admitted to the Department of Neurology or Rheumatology, divided into two groups: CTD-LETM-NMOSD and CTD-LETM-non-NMOSD.…”
Section: Introductionmentioning
confidence: 99%